An Ethylene-Protected Achilles’ Heel of Etiolated Seedlings for Arthropod Deterrence - Boex-Fontvieille, Edouard; Rustgi, Sachin; von Wettstein, Diter; Pollmann, Stephan; Reinbothe, Steffen; Reinbothe, Christiane (Frontiers in Plant Science, 2016)
A small family of Kunitz protease inhibitors exists in Arabidopsis thaliana, a member of which (encoded by At1g72290) accomplishes highly specific roles during plant development. Arabidopsis Kunitz-protease inhibitor 1 (Kunitz-PI;1), as we dubbed this protein here, is operative as cysteine PI. Activity measurements revealed that despite the presence of the conserved Kunitz-motif the bacterially expressed Kunitz-PI;1 was unable to inhibit serine proteases such as trypsin and chymotrypsin, but very efficiently inhibited the cysteine protease RESPONSIVE TO DESICCATION 21. Western blotting and cytolocalization studies using mono-specific antibodies recalled Kunitz-PI;1 protein expression in flowers, young siliques and etiolated seedlings. In dark-grown seedlings, maximum Kunitz-PI;1 promoter activity was detected in the apical hook region and apical parts of the hypocotyls. Immunolocalization confirmed Kunitz-PI;1 expression in these organs and tissues. No transmitting tract (NTT) and HECATE 1 (HEC1), two transcription factors previously implicated in the formation of the female reproductive tract in flowers of Arabidopsis, were identified to regulate Kunitz-PI;1 expression in the dark and during greening, with NTT acting negatively and HEC1 acting positively. Laboratory feeding experiments with isopod crustaceans such as Porcellio scaber (woodlouse) and Armadillidium vulgare (pillbug) pinpointed the apical hook as ethylene-protected Achilles’ heel of etiolated seedlings. Because exogenous application of the ethylene precursor 1-aminocyclopropane-1-carboxylic acid (ACC) and mechanical stress (wounding) strongly up-regulated HEC1-dependent Kunitz-PI;1 gene expression, our results identify a new circuit controlling herbivore deterrence of etiolated plants in which Kunitz-PI;1 is involved.